Evaluating the Efficacy of Therapeutic Interventions for Head Lice: A Systematic Review - Mohamadi, Sarah; Rahimi Khalifeh Kandi, Zahra; Izadkhah, Fatemeh Sadat; Alavi, Fatemeh Sadat; Hazrati-Meimaneh, Zahra; Izadi, Bahare; Mansourian, Morteza (Shahroud Journal of Medical Sciences, 2026)
Background: Pediculosis remains a significant public health concern in many communities. Head lice infestations and their management continue to pose both clinical and social challenges. This systematic review aimed to evaluate the efficacy of various therapeutic interventions for head lice, focusing on their effectiveness in eradicating infestations.Methods: A systematic search was conducted in databases PubMed, Web of Science, and Scopus for studies published between 2013 and 2023, using the keywords Head lice, Pediculus humanus capitis, Pediculosis, and Treatment. Randomized or controlled trials with at least minimal blinding and participants aged over six months were included. Study selection and data extraction were performed independently by two reviewers.Results: A total of 21 studies involving 3,232 participants met the inclusion criteria. Treatments were classified into chemical and non-chemical categories. Among chemical treatments, permethrin, dimethicone, ivermectin, and phenothrin were the most effective. Effective non-chemical interventions included natural oils and plant-based extracts such as eucalyptus. Reported treatment success rates showed considerable variability, ranging from 20% to 100%.Conclusions: Pediculosis remains highly prevalent worldwide. Although various treatment options are available, selecting the most effective and least harmful intervention based on individual and regional factors is essential for optimal management.